Jenis Jenis (Ananas comosus L) Yang Ditanam Di Kabupaten/Kota Prabumulih Sumatera Selatan - Marmaini Marmaini; Syamsul Rizal; Miftahul Jannah (Indobiosains, 2023)
Pineapple is a tropical plant with fresh fruit that has a sweet and slightly sour taste. Pineapple is usually propagated vegetatively by saplings or fruit crown shoots because these plants are pertenocarpic. Plants are nodes that soar upwards. This research was conducted to determine the types of pineapples found in Prabumulih Regency/City and to determine the characteristics of these types of pineapples. This research uses survey method by conducting exploration in Prabumulih Regency/City.